The evolving course of HNF4A hyperinsulinaemic hypoglycaemia—a case series. Issue 1 (12th December 2013) - McGlacken‐Byrne, S. M.; Hawkes, C. P.; Flanagan, S. E.; Ellard, S.; McDonnell, C. M.; Murphy, N. P.
Abstract Background Hepatocyte nuclear factor 4 alpha (HNF4A) gene mutations have a well‐recognized role in maturity‐onset diabetes of the young and have recently been described in congenital hyperinsulinism. A biphasic phenotype has been postulated, with macrosomia and congenital hyperinsulinism in infancy, and diabetes in young adulthood. In this case series, we report three children with HNF4A mutations (two de novo) and diazoxide‐responsive congenital hyperinsulinism, highlighting the potential for ongoing diazoxide requirement and the importance of screening for these mutations even in the absence of family history. Case reports All patients presented with macrosomia (mean birthweight 4.26 kg) and hyperinsulinaemic hypoglycaemia soon after birth (median age 1 day). All three (age range 7 months to 11 years 10 months) remain on diazoxide therapy, with dose requirements increasing in one patient. There was no prior family history of diabetes, neonatal hypoglycaemia or macrosomia. Parents were screened for HNF4A mutations post‐diagnosis and one father was subsequently found to have maturity‐onset diabetes of the young. Conclusions This case series follows the evolving course of three patients with confirmed HNF4A‐mediated congenital hyperinsulinism, highlighting (1) the variable natural history of these mutations, (2) the potential for prolonged diazoxide requirement, even into adolescence, and (3) the need for screening, regardless of family history.